Evidence for in vivo resistance against allopurinol in a dog infected with Leishmania infantum by reduction in copy numbers of the S-adenosylmethionine synthetase (METK) gene - Ingo Schäfer; Mathieu Faucher; Yaarit Nachum-Biala; Lluís Ferrer; Marina Carrasco; Alexandra Kehl; Elisabeth Müller; Torsten J. Naucke; Gad Baneth (Parasites & Vectors)
Abstract Background In Europe, canine leishmaniasis is commonly caused by Leishmania infantum. Allopurinol is the main drug for long-term management of the disease, and clinical relapses of L. infantum infection treated with this drug are described. Resistance to allopurinol has been demonstrated in-vitro, but there is only little knowledge on in vivo resistance in dogs. Findings A two-year-old female spayed Akita Inu that was adopted from a breeding facility near Nice in France was initially diagnosed with primary immune-mediated hemolytic anemia. Immunosuppressive treatment was initiated, and the dog was referred for a second opinion to the Clinique Veterinaire Alliance in France. PCR testing for L. infantum was performed out of EDTA blood and IFA as well as ELISA testing out of serum. Resistance to allopurinol was associated with chromosome and gene copy number (CN) variations including a decrease in the S-adenosylmethionine synthetase (METK) gene CN. Results The dog showed pale mucous membranes, fever (39.1 °C), and a relapse of the anemia. The diagnosis of leishmaniasis was based on the cytological finding of Leishmania amastigotes (bone marrow, spleen, liver), positive PCR testing, and positive IFAT serology. The dog was treated with allopurinol over a period of 1316 days and additionally received two cycles of Glucantime® (meglumine antimoniate), before samples were submitted to the LABOKLIN laboratory to test for resistance against allopurinol. The laboratory work-up revealed mild thrombocytopenia, mild hyperproteinemia with hyperglobulinemia, a marked elevation of the c-reactive protein, and decreased iron concentration. Serum protein electrophoresis showed a polyclonal peak in the gamma globulins. Serology was positive in both ELISA (21.5 LE) and IFAT (1:1024). Quantitative PCR testing of blood was positive with low numbers of Leishmania (10/ml blood) at the timepoint of suspicion for resistance. The urinary protein-to-creatinine ratio was markedly elevated (2.5) and xanthine crystalluria was detected. A CN level of below 3 is considered suspicious for resistance, as revealed in the described Akita Inu dog. Conclusions Relapse of L. infantum infection after applying allopurinol for 1316 days due to resistance was suspected clinically. Positive PCR testing, consistent hematological and biochemistry abnormalities, and reduction in the METK gene CN backed up the clinical suspicion of resistance. Dogs infected with allopurinol resistant strains of L. infantum may represent a great risk for infection of naïve dogs, cats, and humans. Graphical Abstract